Understanding and Promoting Racial Diversity in Healthcare Settings to Address Disparities in Pandemic Crisis Management. (May 2021) - Sarfraz, Azza; Sarfraz, Zouina; Barrios, Alanna; Agadi, Kuchalambal; Thevuthasan, Sindhu; Pandav, Krunal; KC, Manish; Sarfraz, Muzna; Rad, Pedram; Michel, George
Background: Health disparities have become apparent since the beginning of the COVID-19 pandemic. When observing racial discrimination in healthcare, self-reported incidences, and perceptions among minority groups in the United States suggest that, the most socioeconomically underrepresented groups will suffer disproportionately in COVID-19 due to synergistic mechanisms. This study reports racially-stratified data regarding the experiences and impacts of different groups availing the healthcare system to identify disparities in outcomes of minority and majority groups in the United States. Methods: Studies were identified utilizing PubMed, Embase, CINAHL Plus, and PsycINFO search engines without date and language restrictions. The following keywords were used: Healthcare, raci*, ethnic*, discriminant, hosti*, harass*, insur*, education, income, psychiat*, COVID-19, incidence, mortality, mechanical ventilation. Statistical analysis was conducted in Review Manager (RevMan V.5.4). Unadjusted Odds Ratios, P -values, and 95% confidence intervals were presented. Results: Discrimination in the United States is evident among racial groups regarding medical care portraying mental risk behaviors as having serious outcomes in the health of minority groups. The perceived health inequity had a low association to the majority group as compared to the minority group (OR = 0.41; 95% CI = 0.22 to 0.78; P  = .007), and the association of mental health problems to the Caucasian-American majority group was low (OR = 0.51; 95% CI = 0.45 to 0.58; P  < .001). Conclusion: As the pandemic continues into its next stage, efforts should be taken to address the gaps in clinical training and education, and medical practice to avoid the recurring patterns of racial health disparities that become especially prominent in community health emergencies. A standardized tool to assess racial discrimination and inequity will potentially improve pandemic healthcare delivery.